ANALISIS YURIDIS MENGENAI PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN SKINCARE SHARE IN JAR TANPA IZIN EDAR YANG DIJUAL SECARA ONLINE - NIM. A1011191132, EVICENNIA ASRIMUTIA (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractTechnological developments affect international trade and e-commerce. Consumer protection is very important for Share In Jar skincare products without a distribution permit sold online to provide legal certainty. This research examines consumer protection against the circulation of Share In Jar skincare products without a distribution permit sold online, combining preventive and repressive legal approaches.The formulation of the problem that is the focus of the study is